One Biosurfactant-Producing Bacteria Achromobacter sp. A-8 and Its Potential Use in Microbial Enhanced Oil Recovery and Bioremediation - Deng, Zhenshan; Jiang, Yingying; Chen, Kaikai; Li, Jing; Zheng, Chaochao; Gao, Fei; Liu, Xiaodong (Frontiers in Microbiology, 2020)
Biosurfactant plays an important role in bioremediation of crude oil contamination and microbial enhanced oil recovery (MEOR). In the present study, a salt-tolerant, biosurfactant-producing bacterium, designated A-8, was isolated from wastewater contaminated with petroleum collected from the Changqing reservoir in China. A phylogenetic analysis based on the 16S rRNA sequence suggests that strain A-8 belongs to the genus Achromobacter. The optimal growth conditions for strain A-8 in mineral salt (MS) medium were 30℃, pH 7, and 10 g/L NaCl, while the optimal conditions for biosurfactant production in a fermentation medium were 40–45℃, pH 7, and more than 70 g/L NaCl. Better biosurfactant production was obtained from strain A-8 when edible oil and liquid paraffin were used as carbon sources and when (NH4)2SO4 was used as an inorganic nitrogen source compared with other tested carbon and nitrogen sources. The biodegradation of petroleum in MS medium in different optimized conditions reached 56.23%–73.87% for 20 days. The biodegradation of petroleum, together with the production of organic acid and biosurfactant, decreased the viscosity of petroleum by about 45%. The decrease in petroleum viscosity and the biodegradation of petroleum suggest the potential use of strain A-8 for MEOR and bioremediation of petroleum-contaminated environments.